A Case Study of Stress Management Among UiTM Kedah Students / Maizatul Zulaikha Azizan...[et al.] - Azizan, Maizatul Zulaikha; Sahid, Nor Hazirah; Fasiha Onn, Nor Naznin; Abd. Halim, Nurfaiza Asyikin; Abdul Rasid, Nurul Iman (2010)
This study had been carried out to examine the stress management among 288 respondents of student’s UiTM Kedah. Among the selected program which are DPA, DIA, DIB, DIM, DBS, DCS, DQS and DIDE. The research has been conduct in UiTM Kedah. A proportionate stratified random sampling of 288 respondents mainly the UiTM’s students has been selected to study the determine factor of reducing stress. There are several objectives in this research which are to identify the major factor that contributes to stress reduction among students, to analyze the different perspectives among different program on reducing stress and the last objective is to identify the effectiveness of social factor toward reducing stress. From this research, all the objectives achieve successfully. Finding indicates that physiology factor (exercise) is the best way in reducing stress. It is because through exercise, student feels more relax in term of their mind, body and help respondents to balance the attitude and emotion. This also will lead their performance and academic achievement. Lastly, the researchers have made several recommendations for this study which are encourage students exercise every week and suggest sport’s as unit to enhance their function.